Ecological shifts in lagoon patch reefs: consequences of large-scale alterations to coastal systems - Kathleen Sullivan Sealey; Ellery Lennon; Amelia Grace Roskar; Jacob Patus (Academia Biology)
Anthropogenic and climate alterations of coastal environments impact enclosed tropical marine lagoons more directly than offshore marine systems. Long-term studies of lagoonal patch reefs in the central Bahamas were reviewed using a threat assessment matrix to understand spatial and temporal changes in patch reef diversity. A 13-year dataset that includes both epifaunal invertebrate and fish surveys was used to address two research questions: (1) Are there spatial patterns of diversity loss across the tropical lagoon linked to distance from potential land-based sources of pollution? (2) Are there temporal patterns of diversity loss in the tropical lagoon linked to specific storm events or anthropogenic changes over time? The answers to both questions were “yes”; there were spatial and temporal patterns in patch reef diversity, but these patterns were not as expected based on the threat assessment. Patch reefs across a spatial scale contribute individually to the biological diversity and function of the tropical lagoon. Temporal changes were more significant than spatial differences across the lagoon. Fish assemblages showed a significant loss of both species and trophic diversity over time. Changes in the benthic epifauna assemblages supported more weedy, short-lived species, contributing to reduced rugosity, which may have exacerbated declines in fish diversity. Results indicate a need for greater protective measures for the entire Elizabeth Harbour.